THE ANALYSIS OF SATURATED FAT, SODIUM, PROTEIN INTAKE AND BODY MASS INDEX ON THE OCCURRENCE OF HYPERTENSION IN THE ELDERLY IN SEMARANG REGENCY - Hidayah, Arifatul; Yuniastuti, Ari; Ratna Rahayu, Sri (Public Health Perspective Journal, 2020)
Hypertension is the degenerative disease that if not treated immediately, it causes other diseases such as diabetes mellitus, stroke, and so on indeed death as if it does not take any medical treatments.  The prevalence of hypertension on elderly in Central Java in 2018 was 38,4 %. 55-64 years old group was 58,4%, 65-74 years old was 61,6% and >74 years old was 65.6%. The aim of this research is to analyze saturated fat intake, sodium, protein and body mass index related to hypertension on elderly in Semarang Regency. The research used case control design. The sample of the research was 104 respondents obtained by purposive sampling technique. Technique for collecting the data were interview, observation, and questionnaire. Chi square and logistics regression test were used in analyzing the data. The result of the research showed that there were significant influences in the variables of Saturated fat intake (p= 0.019), sodium (p=0.006), protein (0.000), body mass index (0.000) concerning to hypertension on elderly in Semarang Regency. The most influential variable was sodium intake with p=0.006; Exp(B) /OR = 0.295. Thus,  the increase of information about the importance of hypertension prevention is needed.